2013
DOI: 10.1097/spv.0b013e318288ac1c
|View full text |Cite
|
Sign up to set email alerts
|

Communication Barriers Among Spanish-Speaking Women With Pelvic Floor Disorders

Abstract: Objectives: The purpose of our study was to evaluate barriers in communication and disease understanding among office staff and interpreters when communicating with Spanish-speaking women with pelvic floor disorders. Methods: We conducted a qualitative study to evaluate barriers to communication with Spanish-speaking women with pelvic floor disorders among office staff and interpreters. Sixteen office staff and interpreters were interviewed; interview questions focused on experiences with Spanish-speaking pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…Provider-related barriers included poor interpreter knowledge of pelvic floor vocabulary and office staff that interacted with patients but did not have interpreting credentials. System-related barriers included poor access to information [21]. Through focus groups, Spanish-speaking women with POP were more often offered conservative therapies as opposed to English-speakers, who were more often offered surgical management as first-line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Provider-related barriers included poor interpreter knowledge of pelvic floor vocabulary and office staff that interacted with patients but did not have interpreting credentials. System-related barriers included poor access to information [21]. Through focus groups, Spanish-speaking women with POP were more often offered conservative therapies as opposed to English-speakers, who were more often offered surgical management as first-line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work from our group has also found that there are many communication barriers for Latina women with pelvic floor disorders that contribute to a lack of understanding [17]. One of these barriers was the use of interpreters with limited knowledge of the appropriate vocabulary to discuss pelvic floor disorders and the use of non-credentialed interpreters.…”
Section: Discussionmentioning
confidence: 99%
“…These women also faced communication barriers, which have been shown in previous studies to contribute to their lack of understanding. 13 …”
Section: Discussionmentioning
confidence: 99%
“…11,12 One barrier that has been identified is mis-communication secondary to cultural and language differences. 13 …”
mentioning
confidence: 99%